Designing an Ultra-Negative Dispersion Photonic Crystal Fiber with Square-Lattice Geometry. (1st April 2014) - Maji, Partha Sona; Roy Chaudhuri, Partha
Abstract : We have theoretically investigated the dispersion characteristics of dual-core PCF, based on square-lattice geometry by varying different parameters. The fiber exhibits a very large negative dispersion because of rapid slope change of the refractive indices at the coupling wavelength between the inner core and outer core. The dependence of different geometrical parameters, namely, hole-to-hole spacing (Λ ) and different air-hole diameter (d ), was investigated in detail. By proper adjustment of the available parameters, a high negative dispersion value of- 47, 500 ps/nm/km has been achieved around the wavelength of 1550 nm. Our proposed fiber will be an excellent device for dispersion compensation in long-haul data transmission as being thousand times more than the available DCFs.